2018
DOI: 10.1159/000485497
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>V600E BRAF</i></b> versus Non-<b><i>V600E BRAF</i></b> Mutated Lung Adenocarcinomas: Cytomorphology, Histology, Coexistence of Other Driver Mutations and Patient Characteristics

Abstract: Objectives: We analyzed the morphologic features and clinical characteristics of lung adenocarcinomas (ACAs) harboring mutated BRAF. Study Design: A review of the histology/cytology of BRAF-mutated lung ACAs was performed at the Johns Hopkins Hospital from January 1, 2013, to January 1, 2015. Patient demographics, clinical history, and ACA morphology were assessed. Results: Thirty-six cases were identified with a median age of 66 years (range 44-87), 58% (21/36) were female, and 94% (34/36) were current or for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
2
11
2
Order By: Relevance
“…2) was less common (42.9 vs. 72%). In contrast to Salimian et al [1], who observed a more frequent occurrence of BRAF p.V600E mutations in female patients, in our series we did not observe any difference regarding gender. On the other hand, similarly to Salimian et al [1], the occurrence of BRAF non-p.V600E mutations was more frequent in male patients.…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…2) was less common (42.9 vs. 72%). In contrast to Salimian et al [1], who observed a more frequent occurrence of BRAF p.V600E mutations in female patients, in our series we did not observe any difference regarding gender. On the other hand, similarly to Salimian et al [1], the occurrence of BRAF non-p.V600E mutations was more frequent in male patients.…”
contrasting
confidence: 99%
“…In contrast to Salimian et al [1], who observed a more frequent occurrence of BRAF p.V600E mutations in female patients, in our series we did not observe any difference regarding gender. On the other hand, similarly to Salimian et al [1], the occurrence of BRAF non-p.V600E mutations was more frequent in male patients. We also confirmed that BRAF non-p.V600E mutations may be associated with other oncogenic driver mutations; in fact, in 1 case, a non-p.V600E BRAF mutation was identified in association with a KRAS mutation (p.G12S).…”
contrasting
confidence: 99%
See 3 more Smart Citations